Strategi Komunikasi Pemasaran Es Teh Solo 1987 Cabang Warakas dalam Membangun Brand Image - Kurnia Suci, Intan; Yanis, Fauziah (Green Publisher Indonesia, 2024)
Brand image has an important role in delivering the company to its goals or targets. Currently, the competition in the iced tea cold drink market is very tight and mushrooming everywhere so that this is the cause of Iced Teh Solo 1987 experiencing a consistent decline in sales in recent months. These problems should be solved through strengthening the brand image so that customer trust can be built. This study aims to analyze the marketing communication strategies carried out by Es Teh Solo 1987 Warakas branch in building a brand image. This research was completed using a descriptive qualitative method with data collection techniques through observation and interviews. The data analysis techniques used in this study are in the form of the reduction stage and the presentation stage. The results of this study show that Es Teh Solo 1987 uses five ways to maintain its brand image as a cheap and affordable brand. The five ways are through personal sales, events and experiences, public relations, sales promotion, and corporate branding.